IMPLEMENTING ESG CONCEPT IN SHARIA STOCK SCREENING PROCESS - Rifka Mustafida; Najim Nur Fauziah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2021)
Islam places great importance on moral, environmental and social dimension. Sustainable development is centric to the overlapping factors both Islamic finance and Socially Responsible Investment, which are the economy, the environment and social impact. In contrary, Empirical evidence concerning ESG practice of IFIs and Sharia compliant companies is still lacking. The investment portfolio should therefore be scrutinized on the criteria of justice, social welfare and sustainability. This paper aims to identify sustainability report of Sharia Stocks companies and propose i-ESG index for sharia stocks screening in Indonesia. A qualitative study is used to describe sustainability action doing by Sharia compliant companies listed on Indeks Saham Syariah Indonesia (ISSI) in October 2019. This study found that, almost all the companies shows their Good Corporate Governance, but only a few of company have their sustainability report. Therefore a novel parameter to screen the sharia stocks screening process is urgently needed.Â Â